(untitled) (Research, Society and Development, 2020)
The surgical procedure for the clinical crown lengthening, aims for an aesthetic or functional form to compensate for the reabsorption of the alveolar bone tissue caused by the invasion of the biological space. The conditions that must be taken into account during surgical planning are related to an excessive gingival exposure, altered passive eruption and lack of height of the dental element for restorative purposes. The objective of this systematic review was to evaluate in the scientific literature the minimally invasive surgical techniques used to clinical crown lengthening. A systematic review of the literature was performed using the databases, Science Direct, Embase, Cochrane Collaboration Library, and PubMed/MEDLINE. The search strategy provided a total of 157 studies. After selection, five articles met all the inclusion criteria and were included in this systematic review. Studies have shown that conventional surgical techniques for clinical crown lengthening are presented as an effective approach that promotes good aesthetic and functional results. However, they have some limitations. After evaluating the minimally invasive surgical techniques included in this systematic review, it was possible to infer that they presented satisfactory results in the soft and hard tissue contouring, with no complications and dissatisfaction being observed by the patients.